2022
DOI: 10.1007/s00429-022-02602-x
|View full text |Cite
|
Sign up to set email alerts
|

Is musical engagement enough to keep the brain young?

Abstract: Music-making and engagement in music-related activities have shown procognitive benefits for healthy and pathological populations, suggesting reductions in brain aging. A previous brain aging study, using Brain Age Gap Estimation (BrainAGE), showed that professional and amateur-musicians had younger appearing brains than non-musicians. Our study sought to replicate those findings and analyze if musical training or active musical engagement was necessary to produce an age-decelerating effect in a cohort of heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…As music can directly speak to both the emotional brain and to the intellect and has a strong social component its fundamental spiritual significance is comprehensible. Additionally, there is a remarkable transfer of positive effects for those engaging in musical training and listening to music ( Matziorinis et al, 2022 ).…”
Section: Dance Music and Emotion In Dementia: Movements Of Expression...mentioning
confidence: 99%
“…As music can directly speak to both the emotional brain and to the intellect and has a strong social component its fundamental spiritual significance is comprehensible. Additionally, there is a remarkable transfer of positive effects for those engaging in musical training and listening to music ( Matziorinis et al, 2022 ).…”
Section: Dance Music and Emotion In Dementia: Movements Of Expression...mentioning
confidence: 99%
“…A recent randomised controlled trial (RCT) found that playing a musical instrument (the piano), can help preserve the integrity of the fornix in older adults, with a weak positive association with episodic memory (Jünemann et al, 2022 ; see also Burzynska et al, 2017 ). Some evidence also suggests that musical activities may support the preservation of brain volume in prefrontal and temporal regions (Chaddock‐Heyman et al, 2021 ; for review, see also Muiños & Ballesteros, 2021 ) and reduce overall signs of structural ageing at non‐professional level (Chaddock‐Heyman et al, 2021 ; Rogenmoser et al, 2018 ; however, see also Matziorinis et al, 2022 ). However, a systematic account on the influence of music on brain structure and its association with cognitive function in healthy ageing is currently missing (for review, see Sutcliffe et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors are among the easiest to modify (von Haumeder et al, 2019). More specifically, participation in cultural and artistic activities, including playing and listening to music, is often consider a resilience factor (Matziorinis et al, 2022). While reactions to a stressor depend on both pre-and post-traumatic resilience factors (Kalisch et al, 2017), most studies have explored the benefits of musical activity after the occurrence of a traumatic event as an intervention tool to reduce the intensity of PTSD, and not before as a preventive tool against the deleterious effects of potential exposure to a traumatic situation (Landis-Shack et al, 2017;Pant et al, 2022).…”
Section: Introductionmentioning
confidence: 99%